2014
DOI: 10.1155/2014/981312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ocular and Auditory Manifestations of Congenital Rubella Syndrome in Mbingo

Abstract: Purpose. Congenital rubella syndrome (CRS) is a global cause of preventable hearing impairment, blindness, and intellectual impairment. The present study sought to identify ocular and auditory manifestations of CRS in school-aged children in Mbingo, Cameroon. Design. Cross sectional study. Subjects. Students at two schools, one for children with hearing impairment, were screened for cataract, congenital glaucoma, and pigmentary retinopathy. Methods. Students underwent seven-field digital fundus photography thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…The authors recruited 320 children from two different schools in the Northwest region of Cameroon, including one school for the deaf. They found that hearing-impaired children were seven times more likely to have positive rubella IgG serology (48.7%) than children with normal hearing (7.4%; p < 0.0001) [40].…”
Section: Etiologies Of Hearing Impairment In Cameroonmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors recruited 320 children from two different schools in the Northwest region of Cameroon, including one school for the deaf. They found that hearing-impaired children were seven times more likely to have positive rubella IgG serology (48.7%) than children with normal hearing (7.4%; p < 0.0001) [40].…”
Section: Etiologies Of Hearing Impairment In Cameroonmentioning
confidence: 99%
“…Pure tone audiometry (PTA) was the most frequent tool used to diagnose HI. The study quality was high, moderate and low in ten [26][27][28][29][30][31][32][33][34][35], three [36][37][38] and four [39][40][41][42] studies, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational age at time of confirmed rubella infection, clinical manifestation of congenital rubella syndrome and vertical transmission rate . [Colour figure can be viewed at wileyonlinelibrary.com…”
Section: Discussionmentioning
confidence: 99%
“…Classical postnatal manifestations of congenital rubella syndrome are deafness, cataract and cardiac anomalies, but this is only typical for early infection prior to 11 weeks. As the gestational age at rubella infection increases, rates of vertical transmission decrease and the fetal manifestations of congenital rubella syndrome become less severe 15 (Figure 7). Other prenatal features include intrauterine growth restriction, multi-cystic kidney, meconium peritonitis, hepatosplenomegaly and microcephaly with intracranial calcifications.…”
Section: Causesmentioning
confidence: 99%